Analysis of the downstream mediators of toll-like receptor 3-induced apoptosis in labial salivary glands in patients with Sjögren's syndrome. Issue 1 (2nd January 2016) - Horai, Yoshiro; Nakamura, Hideki; Nakashima, Yoshikazu; Hayashi, Tomayoshi; Kawakami, Atsushi
Abstract : Objectives. The aim of this study was to clarify the molecular mechanisms elicited by toll-like receptor (TLR)3 in salivary gland cell death in patients with SS. Methods. Expression of TLR3 and its downstream molecules was examined by immunohistochemical analysis, immunofluorescence, Western blot (WB), and antibody dot-blot array in labial salivary glands (LSGs), and cultured primary salivary gland epithelial cells (SGECs) obtained from patients with SS. We also investigated the difference of expression between ducts/alveoli of LSGs and cultured SGECs. Results. Phosphorylated Fas-associated protein with death domain (p-FADD) or caspase-8 was not found in ducts or alveoli of LSGs from SS patients and controls. Weak expression of receptor-interacting serine/threonine-protein kinase 3 (RIPK3) was found in SS patients, whereas no staining was observed in LSGs of controls. In contrast to LSGs, stimulation of SGECs with polyinosinic:cytidylic acid (poly I:C) significantly induced the expression of RIPK3, p-FADD, and cleaved caspase-8 by immunofluorescence and RIPK3, p-FADD, and cleaved caspase-3 by WB. However, it was counteracted by epidermal growth factor (EGF). Co-localization of anti-apoptotic molecules hemeoxygenase-2, heat shock protein 27, and p-protein kinase B or p-Akt was induced in EGF-stimulated SGECs. Conclusions. We observed that poly I:C induced apoptosis of SGECs in vitro compared with a relatively low prevalence of apoptosis found in the ducts and alveoli of LSGs in vivo . Thus, we speculate that other counter-regulatory mechanisms, including those induced by EGF, might exist to protect against TLR3-mediated apoptosis of ductal and acinar epithelial cells in vivo .